Multiple Perspectives: A Guide to Qualitative Research in Music Therapy - Smeijsters, Henk (Barcelona Barcelona Publishers, 1997)
A comprehensive and insightful survey of existing approaches to qualitative research in music therapy. The author begins by comparing qualitative and quantitative paradigms; he then introduces the reader to single-case designs. In the rest of the book, Dr. Smeijsters provides a probing and thoughtful analysis often examples of qualitative research, pointing out significant theoretical and methodological issues, while also offering sensitive and personal commentary on each approach. Drawing upon his extensive experience in clinical music therapy research, Dr. Smeijsters gives enormous breadth and depth of perspective to the diversity already evident in the field. Reading the book is like taking a journey through the forest with a guide continually pointing out what to notice. The language is straightforward, and the dialogue is personal. This book is certainly one of the landmarks in the forest.